Isolation from natural habitat reduces yield and quality of passion fruit. (23rd October 2018) - Silva, S. R.; Almeida, N. M.; de Siqueira, K. M. M.; Souza, J. T.; Castro, C. C.
Abstract: Loss and fragmentation of native vegetation negatively affect crop pollinators and productivity of several crop species. The yellow passion fruit is an excellent model to investigate this issue, because its main pollinators are sensitive to deforestation. Seasonality also influences fruit set of crop species that are pollinated by bees. Climate determines plant flowering patterns and consequently affects pollinator activity. Little is known on effects of pollinators on crop quality in general, and particularly of many tropical fruits that have multiple fruiting seasons throughout the year, such as passion fruit. Our hypothesis is that the distance to the native vegetation and climate seasonality affect the pollination and fruit production of cultivated, hermaphrodite, self‐incompatible, protandrous species that depend on large‐sized bees to set fruit. We observed flowers of the yellow passion fruit in eight areas at different distances (600–4, 000 m) from a dry seasonal forest ( Caatinga ). We compared the frequency of the main floral visitor (pollinators and robbers) visits and fruit set among areas at the beginning and end of the dry and rainy seasons. Xylocopa species were pollinators, and Apis mellifera, Trigona spinipes and a hummingbird were robbers. Xylocopa visits diminished with increasing distance to native remnants, converse to what was observed for the robbers at the beginning of the dry season. Fruit set was higher at the beginning of the dry season. The distance to the forest affected quality of fruits in terms of length, diameter and skin thickness, which all decreased with increase in remnant distance. Our results show that insect pollination is higher in the dry season, increasing profitability and reducing labour costs for the producer. Considering the influence of distance to native vegetation on pollination, robbery and fruit quality, our study reinforces the necessity for conservation of native vegetation remnants.